Behaviour and natural history of the West Indian Whistling-Duck Dendrocygna arborea on Long Island, Bahamas - Staus, Nancy L (Wildfowl, 1998)
The West Indian Whistling-duck is a sedentary species, endemic to the West Indies. Threatened by hunting, habitat destruction and introduced predators, the bird is classified as vulnerable by the International Union for the Conservation of Nature (IUCN) with fewer than 10,000 individuals remaining. Despite its near-threatened status and wide range in the Caribbean, the biology of the species is poorly known. I studied the behaviour of the West Indian Whistling-duck during three summers (1993-1995) on Long Island and Hog Cay, Bahamas, to provide baseline ecological data for conservation planning and development of future research priorities. Breeding on Long Island occurred from February through July, with nesting peaks in April and June. Nests were leaf-lined depressions on the ground, each containing 6-10 cream-colored eggs. Both parents incubated, alternating 24-hour shifts, and both cared for the young. In two cases, pair bonds lasted at least two years. Adults fed at an artificial feeding station and on natural wetlands; ducklings fed by diving and dabbling. Population means ranged from 513 to 1,071 for 1994 and 1995, respectively. Adults had a yearly survival rate of 64%. Brood size decreased between age-class I and just-fledged juveniles.